The Highs and Lows of the Minimum Wage Effect: A Time‐Series Cross‐Section Study of the Canadian Law - Baker, Michael; Benjamin, Dwayne; Stanger, Shuchita (Journal of Labor Economics, 1999)
We examine the effects of minimum wage legislation in Canada over the period 1975–93. For teenagers we find that a 10% increase in the minimum wage is associated with roughly a 2.5% decrease in employment. We also find that this result is driven by low frequency variation in the data. At high frequencies the elasticity is positive and insignificant. The difference in the elasticity across the bandwidth has implications for the interpretation of employment dynamics as a result of minimum wage policy and experimental design in minimum wage studies. It also provides a simple reconciliation of the ‘‘new minimum wage research,’’ which reports very small negative, or positive, elasticities.